Effect of Coating on Quality of Okra Seeds in Storage - PRATIBHA PARIHAR; KC DHIMAN; RK KAPILA; RAJESH KANWAR (Seed Research, 2026)
Preserving the planting value of the seed from harvest to next sowing is an integral component of seed industry. It is important to keep intact the physiology of the seed throughout the storage period through various dynamic technological interventions that could result in optimum field stand. Seed coating is one such simple and efficient technology for maintaining seed physiology and health during storage. The seeds of ‘P-8’ variety of okra were coated with nine different treatments comprising of polymer, fungicides, insecticide, polymerfungicides and polymer-insecticide combinations and there after stored in HDPE (high density polyethylene) inter woven non-laminated bags for 12 months. Amongst various treatments, seed coated with polymer @ 3 ml per kg of seed and vitavax 200 @ 2 g per kg of seed recorded the highest germination percentage (95.00%), rate of germination (44.83), seedling length (28.80 cm), seedling dry weight (0.246 g), seedling vigour index (2755), field emergence (84.00%) and lowest electrical conductivity (0.829 m mho/cm/g) at the end of 12 months of storage over the untreated control. Lower seed infection (0%) was recorded in treatments over untreated control (2.00%). The present study concluded that okra seeds coated with polymer @ 3 ml per kg of seed and vitavax 200 @ 2 g per kg of seed and packed in high density polyethylene (HDPE) interwoven non-laminated bag could help in maintaining the seed quality up to 12 months of storage under ambient conditions of Palampur.